2014
DOI: 10.1021/ci500197a
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Aided Discovery of Aromatic l-α-Amino Acids as Agonists of the Orphan G Protein-Coupled Receptor GPR139

Abstract: GPR139 is an orphan G protein-coupled receptor expressed mainly in the central nervous system. We developed a pharmacophore model based on known GPR139 surrogate agonists which led us to propose aromatic-containing dipeptides as potential ligands. Upon testing, the dipeptides demonstrated agonism in the Gq pathway. Next, in testing all 20 proteinogenic l-α-amino acids, L-tryptophan and l-phenylalanine were found to have EC50 values of 220 and 320 μM, respectively, making them the first putative endogenous agon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(79 citation statements)
references
References 24 publications
2
77
0
Order By: Relevance
“…It has been shown to have a high mRNA expression in the brain, particularly in the striatum and hypothalamus678 – suggesting that GPR139 could be involved in movement control789 and/or the regulation of food intake/metabolism610. GPR139 is thus a potential target for the treatment of Parkinson’s disease, obesity, eating disorders, and/or diabetes.…”
mentioning
confidence: 99%
“…It has been shown to have a high mRNA expression in the brain, particularly in the striatum and hypothalamus678 – suggesting that GPR139 could be involved in movement control789 and/or the regulation of food intake/metabolism610. GPR139 is thus a potential target for the treatment of Parkinson’s disease, obesity, eating disorders, and/or diabetes.…”
mentioning
confidence: 99%
“…Additionally, this reaction could be inhibited by a G q/11 selective inhibitor [2] . This observation was confirmed through the discovery of a series of GPR139 agonists using calcium mobilization assays [7,8] . Susens et al identified the signal transduction pathway using both Ca 2+ mobilization and luciferase-reporter-gene assays.…”
Section: Resultsmentioning
confidence: 80%
“…However, Hu et al identified GPR139 as a Gs-coupled receptor because overexpressed GPR139 in HEK239 cells could increase basal intracellular cAMP concentrations [6] . Previous studies have shown that Gq-coupling is the main signaling pathway of GPR139 and might activate other pathways [8] . Furthermore, it was noted that GPR139 appears to be a monomer in HEK-293 cells and a dimer in CHO-K1 cells [3] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we investigated the binding of To avoid the high level of binding to the lters and potential low specic binding due to a fast off-rate of the radioligand; SPA-bead binding, centrifugation-binding and whole cell binding was attempted, but none of these methods gave any GPR139 is expressed at the protein level in the CHO-k1 GPR139 cell line, as we have previously demonstrated a functional agonist response to 1 in the same cell line, 9 which was conrmed in the present study. Using qPCR analysis we furthermore veried the presence of GPR139 transcripts in the CHO-k1 GPR139 cell line but not in the CHO-k1 background cell line (Fig.…”
Section: Recombinant Gpr139 Cho-k1 Cell Linementioning
confidence: 99%